An Investigation of Students Attitude and Motivation toward Online Learning - Evelyn Knowles, PhD; Dennis Kerkman, PhD (Park University, 2007)
This study investigated students' attitudes and motivations toward online learning. Students in the online course, Introduction to the Visual Arts, were asked to complete questionnaires administered during the first and last week of the online course. A group of questions on Attitude was asked on both surveys. Questions on Interest, Self-management, and Locus of Control were asked only at the beginning of the course. The end of class survey included questions on Study Process Approach. Students in the study were found to have a strong internal Locus of Control. A significant correlation was found between a more internal locus of control and relying on surface strategies for learning. Another significant result was found on the Attitude pre- and post-course comparison regarding missing interaction with other students and getting more information through an online course. Generally, students' attitude toward online learning was more positive during the last week of the course than in the first week. The study showed that this online course provided a sufficient amount of student to instructor interaction, a high amount of student to material interaction, and a low amount of student to student interaction.